(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Spontaneous coronary artery dissection (SCAD) is a rare and non-atherosclerotic cause of acute coronary syndrome, myocardial infarction, and sudden death, typically affecting young women without traditional risk factors for cardiovascular disease. Risk factors differ from atherosclerotic disease, being associated with female sex, pregnancy, physical and emotional stress, and concomitant systemic arteriopathies, particularly fibromuscular dysplasia. Objectives: To demonstrate a rare etiology of acute myocardial infarction caused by spontaneous coronary artery dissection in a patient without risk factors for coronary artery disease. Additionally, to highlight the importance of early and differential diagnosis, as well as discuss treatment and associated outcomes. Methods: A descriptive observational study whose data were obtained from medical records. The research was conducted at Cassiano Antônio Moraes University Hospital. Results: We report the case of a young patient without risk factors, admitted for SCAD of the anterior descending artery. The patient received conservative treatment and is asymptomatic without recurrence of the segmental disease 32 months after the primary event. Conclusion: SCAD is a clinical entity underdiagnosed both due to the low index of suspicion and the lack of familiarity with its angiographic variants. Early and adequate diagnosis is essential due to the potential for sudden cardiac death and increased risk of future cardiac events, including recurrent dissection.